Ethiopia : Potential of Traditional Social Insurance for Supporting Health Care - Haile Mariam, Damen (World Bank, Washington, DC, 2012)
This report deals with a community based alternative to health care financing called "eder." Eder is a form of traditional social institution in Ethiopia that is established by the mutual agreement and assistance of community members in order to collaborate with each other whenever any member of their family faces adverse situations. The primary function of the eder is taking care of the burial of members, as well as acting as health insurers. Eders raise funds and coordinate free labor of members in activities such as building roads, schools, health institutions, etc. They contribute money to members who have lost their houses in a fire or experience farming loss, and provide assistance to cover their medical costs. Eders also have provisions for pensioned members who face economic problems and are unable to pay contributions.